Analysis on Quality of Learning in e-learning Platforms - Veeramanickam Murugappan M.R; Rajakumar B R; Binu D; Ramesh P. (International Journal of Engineering Education, 2021)
This paper plans to introduce a model that concerns on e-learning quality management system under two phases: (i) Questionnaire preparation and (ii) Predicting the impact of e-learning quality. In order to analyze the quality of learning in e-learning platform, initially, the questionnaire will be prepared with respect to various drivers such as (i) Degree of flexibility and adaptability, (ii) Degree of supportability (students and staffs) (iii) Staff qualification and experience, (iv) Performance assessment and (v) Learner’s interest. The first driver includes factors like learner control, learner activity, motivation and feedback. The second driver includes factors like technical skills, cost and technical crisis and internet access. The third driver includes factors like awareness of new technology, whether the team includes instructional designers, multimedia procedures and so on. The fourth driver (Performance assessment) includes the impact of performance evaluation by means of Artificial Intelligence (AI) methods. The fifth driver includes factors like course materials, gaming and learners self interest. The prepared questionnaire is distributed to different age group people and are demanded to fill up the precise information as much as possible. These responses from the people are then taken for analysis purpose. In this research work, the analysis is carried out based on SEM analysis, which is a way to identify the learning quality in e-learning platform.